2021
DOI: 10.1055/a-1673-0708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Pandemic on Well-Baby Nursery

Abstract: BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic is associated with fewer deliveries and premature births; however, the impact of this pandemic on the well-baby nursery (WBN) is unknown. OBJECTIVE: To evaluate the impact of the COVID-19 pandemic on infants admitted to the WBN by comparing pandemic and pre-pandemic cohorts. STUDY DESIGN: We performed a retrospective study of infants admitted to a WBN during the pandemic period (March 18, 2020-to-March 17, 2021) and compared them to those during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Possible explanations include stress and anxiety during the pandemic, as parents were more likely to delay or postpone pregnancy or to have fewer children, and restricted access to fertility clinics. Our finding was consistent with other studies from well‐baby nurseries 19 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Possible explanations include stress and anxiety during the pandemic, as parents were more likely to delay or postpone pregnancy or to have fewer children, and restricted access to fertility clinics. Our finding was consistent with other studies from well‐baby nurseries 19 …”
Section: Discussionsupporting
confidence: 94%
“…Our finding was consistent with other studies from well-baby nurseries. 19 Duration of MOM provision in VLBW infants did not differ be- The authors explored their study population for indicators of socioeconomic deprivation and found an increase in MOM for the private insurance group. 16 In a related study, a large cohort of infants admitted to two neonatal units before and during the TA B L E 1 Parental and infant characteristics.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have shown no change in NICU admissions (24,28) and specifically a decrease in NICU admissions (29)(30)(31) for term infants during the COVID-19 pandemic. Differences in patient demographics may explain the differences between our study and others: we have a higher maternal hypertension rate (22%-26%), number of Hispanics (68%-73%), and majority of our patients are on public insurance.…”
Section: Nicu Admissionsmentioning
confidence: 94%